SUPPLY CHAIN RISK MITIGATION OF STAKEHOLDER TUNA FLOSS USING HOUSE OF RISK METHOD - Muhamad Rusman; Syarifuddin Mabe Parenreng; Dwi Handayani; A. Maulisyah (Center for Study and Journal Management FTI UMI, 2023)
Tuna floss is a processed food that is a popular product. As a manufacturer, KWN Fatimah Az-Zahrah is required to make quality products. The supply chain activity of tuna floss will be faced with various risks. Thus, supply chain risk management is needed for the stakeholders involved, which consist of suppliers, manufacturers, distributors, and retailers to prevent the risks. This research aims to identify risk events and risk agents for stakeholders, evaluate the priority of the risk agents for stakeholders, and design effective mitigation for stakeholders. The method used is the House of Risk (HOR), which is divided into 2 parts: HOR 1 is for determining risk agents priority based on Aggregate Risk Potential (ARP) values, while HOR 2 is for determining mitigation action based on level of effectiveness. The Supply Chain Operation Reference (SCOR) to mapped the risks. The results of HOR showed 7 priority risk agents and 11 mitigation for suppliers, 11 priority risk agents and 22 mitigation for manufacturers, 5 priority risk agents and mitigation for distributors, 3 priority risk agents and 5 mitigation for retailers that are effective in reducing the probability of the occurrence of risk agents in the supply chain of tuna floss.